Mass gap for a monopole interacting with different nonlinear spinor fields - Dzhunushaliev, V.; Folomeev, V.; Abdykaliyeva, A.; Khussainova, S.; Temirova, A. (Recent Contributions to Physics, 2022)
We study the properties of the mass gap for monopole solutions in SU(2) Yang-Mills theory with a source of the non-Abelian gauge field in the form of a spinor field described by the nonlinear Dirac equation. Different types of nonlinearities parameterized by the parameter λ are under consideration. It is shown that for the range of values of this parameter studied in the present paper the value of the mass gap depends monotonically on this parameter, and the position of the mass gap does not practically depend on λ.In the present paper we study the dependence of the size of a mass gap, its position, etc., on the value of a parameter describing the nonlinear self-interaction potential of the spinor field.By the term a position of the mass gap, we mean the value of the frequency E, for which the energy spectrum has a minimum. It is of interest to note that the position of the mass gap E,  does not practically depend on the nonlinearity parameter λ. One can assume that in fact this is the case, and deviations from this value are related to errors in numerical calculations. It is of interest that the position of the mass gap does not practically depend on the value of the nonlinearity parameter, at least in the range of values of the spinor field nonlinearity parameter considered here.
Keywords: non-Abelian SU(2) theory; nonlinear Dirac equation; monopole; energy spectrum; mass gap; nonlinearity parameter